Neural-specific carbohydrate moiety shared by many surface glycoproteins in Drosophila and grasshopper embryos - PM Snow; Nipam H. Patel; A L Harrelson; CS Goodman (1987)
Antiserum against horseradish peroxidase (anti-HRP Ab) labels the surfaces of neurons in both Drosophila and grasshopper (Jan and Jan, 1982). Here we show that the anti-HRP Ab (1) immunoprecipitates at least 17 different membrane glycoproteins from the Drosophila embryo CNS (and a similar array from grasshopper), and (2) recognizes a neural-specific carbohydrate moiety expressed by most if not all of these proteins. Although the anti-HRP Ab stains all axon pathways, 2 of the anti-HRP glycoproteins, fasciclin I and II, are expressed on specific subsets of axon pathways in the grasshopper embryo.